Struktur Kognisi Tentang Polisi (Studi Tiga Tahap Perkembangan Kanak-Kanak) - Meliala, Adrianus (Makara Human Behavior Studies in Asia, 2003)
The aim of this research is to investigate cognitive profile on police based on the view of children from three different developmental stages. It is hypothesized that the more older children are the more knowledgeable they are in relation to the police’s role and its typology and function.The result shows that the elder group of students indicate better knowledge and more understanding in terms of the police and what they normally do.